Entrectinib in patients with advanced or metastatic NTRK fusion-positive solid tumours: integrated analysis of three phase 1–2 trials. Issue 2 (February 2020) - Doebele, Robert C; Drilon, Alexander; Paz-Ares, Luis; Siena, Salvatore; Shaw, Alice T; Farago, Anna F; Blakely, Collin M; Seto, Takashi; Cho, Byung Chul; Tosi, Diego; Besse, Benjamin; Chawla, Sant P; et al.
Summary: Background: Entrectinib is a potent inhibitor of tropomyosin receptor kinase (TRK) A, B, and C, which has been shown to have anti-tumour activity against NTRK gene fusion-positive solid tumours, including CNS activity due to its ability to penetrate the blood–brain barrier. We present an integrated efficacy and safety analysis of patients with metastatic or locally advanced solid tumours harbouring oncogenic NTRK1, NTRK2, and NTRK3 gene fusions treated in three ongoing, early-phase trials. Methods: An integrated database comprised the pivotal datasets of three, ongoing phase 1 or 2 clinical trials (ALKA-372-001, STARTRK-1, and STARTRK-2), which enrolled patients aged 18 years or older with metastatic or locally advanced NTRK fusion-positive solid tumours who received entrectinib orally at a dose of at least 600 mg once per day in a capsule. All patients had an Eastern Cooperative Oncology Group performance status of 0–2 and could have received previous anti-cancer therapy (except previous TRK inhibitors). The primary endpoints, the proportion of patients with an objective response and median duration of response, were evaluated by blinded independent central review in the efficacy-evaluable population (ie, patients with NTRK fusion-positive solid tumours who were TRK inhibitor-naive and had received at least one dose of entrectinib). Overall safety evaluable population included patients from STARTRK-1, STARTRK-2, ALKA-372-001, and STARTRK-NG (NCT02650401 ; treating young adult and paediatric patients [aged ≤21 years]), who received at least one dose of entrectinib, regardless of tumour type or gene rearrangement. NTRK fusion-positive safety evaluable population comprised all patients who have received at least one dose of entrectinib regardless of dose or follow-up. These ongoing studies are registered with ClinicalTrials.gov, NCT02097810 (STARTRK-1) and NCT02568267 (STARTRK-2), and EudraCT, 2012–000148–88 (ALKA-372-001). Findings: Patients were enrolled in ALKA-372–001 from Oct 26, 2012, to March 27, 2018; in STARTRK-1 from Aug 7, 2014, to May 10, 2018; and in STARTRK-2 from Nov 19, 2015 (enrolment is ongoing). At the data cutoff date for this analysis (May 31, 2018) the efficacy-evaluable population comprised 54 adults with advanced or metastatic NTRK fusion-positive solid tumours comprising ten different tumour types and 19 different histologies. Median follow-up was 12.9 months (IQR 8·77–18·76). 31 (57%; 95% CI 43·2–70·8) of 54 patients had an objective response, of which four (7%) were complete responses and 27 (50%) partial reponses. Median duration of response was 10 months (95% CI 7·1 to not estimable). The most common grade 3 or 4 treatment-related adverse events in both safety populations were increased weight (seven [10%] of 68 patients in the NTRK fusion-positive safety population and in 18 [5%] of 355 patients in the overall safety-evaluable population) and anaemia (8 [12%] and 16 [5%]). The most common serious treatment-related adverse events were nervous system disorders (three [4%] of 68 patients and ten [3%] of 355 patients). No treatment-related deaths occurred. Interpretation: Entrectinib induced durable and clinically meaningful responses in patients with NTRK fusion-positive solid tumours, and was well tolerated with a manageable safety profile. These results show that entrectinib is a safe and active treatment option for patients with NTRK fusion-positive solid tumours. These data highlight the need to routinely test for NTRK fusions to broaden the therapeutic options available for patients with NTRK fusion-positive solid tumours. Funding: Ignyta/F Hoffmann-La Roche.